The unique immune microenvironment of liver metastases: Challenges and opportunities. (June 2021) - Ciner, Aaron T.; Jones, Keaton; Muschel, Ruth J.; Brodt, Pnina
Abstract: Liver metastases from gastrointestinal and non-gastrointestinal malignancies remain a major cause of cancer-related mortality and a major clinical challenge. The liver has unique properties that facilitate metastatic expansion, including a complex immune system that evolved to dampen immunity to neoantigens entering the liver from the gut, through the portal circulation. In this review, we describe the unique microenvironment encountered by cancer cells in the liver, focusing on elements of the innate and adaptive immune response that can act as a double-edge sword, contributing to the elimination of cancer cells on the one hand and promoting their survival and growth, on the other. We discuss this microenvironment in a clinical context, particularly for colorectal carcinoma, and highlight how a better understanding of the role of the microenvironment has spurred an intense effort to develop novel and innovative strategies for targeting liver metastatic disease, some of which are currently being tested in the clinic.